Acute Venom Toxicity Determinations for Five Iranian Vipers and a Scorpion - Behrooz Fathi; Fatemeh Younesi; Fatemeh Salami (Iranian Journal of Toxicology, 2022)
Background: Poisoning due to the bites and stings of venomous snakes and scorpions is a neglected public health problem, particularly in rural areas. Poor health facilities and inadequate knowledge of health care personnel are the major factors that result in envenomated human victims not receiving adequate care and medical attention. There is a great need for up-to-date and effective healthcare knowledge and awareness of the potency and lethality of venomous creatures in Iran. Assessment of the potency, acute toxicity, and lethal effects of venomous creatures come from a variety of specific tests, such as the 50% median lethal dose (LD50) and ample animal experimentations. Methods: In the present study, using modified Reed-Muench method, the LD0, LD50, and LD100 values of the venoms from five Iranian vipers and one scorpion were determined. The studied venomous creatures were: Macrovipera lebetina, Vipera albicornuta, Vipera raddei, Caucasicus intemedius agkistrodon, Montivipera latifii, and one scorpion Hemiscorpius lepturus. The venoms were injected in Albino mice (n=204) intraperitoneally, and their toxicities determined. Results: The results revealed that the LD50 values of the above-mentioned creatures were 3.87, 2.05, 1.63, 1.45, 0.84, and 6.33 mg/kg, respectively. Among the vipers, M. latifii had the most potent venom while M. lebetina’s venom had the lowest toxicity. Conclusion: Theoretically, the determined LD50 values provide for objective comparisons of the toxicity among of the venoms. However, comparison becomes complicated due to variations in the venoms’ LD50. Further, based on the venoms’ toxicity levels, H. lepturus’ venom caused the lowest toxicity in the Albino mice.